Enhancing final-year medical students' clinical examinations performance via a transdiagnostic ACT-based intervention - Tze, Nicholas Ping Pang; Koh, Eugene; Mohd Kassim, Mohd Amiruddin; Shoesmith, Wendy Diana; Kamu, Assis; Ho, Chong Mun; Ng, Jun Rong; Wider, Walton (Multidisciplinary Digital Publishing Institute, 2022)
Introduction: Performance anxiety is a transdiagnostic construct similar in both sports and clinical medical examinations. Given that acceptance and commitment therapy (ACT) and other similar therapies have transdiagnostic evidence in improving the performance of athletes, the same approach can be adopted for medical students in improving their performance during clinical examinations. This pilot study aimed to assess the efficacy of a brief ACT-based intervention in improving transdiagnostic performance anxiety in clinical medical students through assessing changes in psychopathology scores (depression, anxiety, and stress) and psychological process variables (psychological flexibility, cognitive fusion, and mindfulness). Methods: Final-year medical students were randomized into intervention and control groups. A one-day ACT-based intervention was delivered to an intervention group, with the control group crossing over one month post intervention. Both groups filled in sociodemographic questionnaires and questionnaires measuring psychological flexibility, cognitive fusion, mindfulness, depression, anxiety, and stress at three time points: T1 (before intervention), T2 (immediately after intervention), and T3 (one month post intervention). Repeated measures ANOVA was employed to assess the change between the intervention and control groups over time. Results and Conclusions: There was a significant change in anxiety scores from T1 to T3. In addition, there were significant improvements in mindfulness, cognitive fusion, and psychological flexibility scores over time in the intervention group compared with the control group. This pilot study builds on small single-sample evidence bases for the efficacy of an ACT-based intervention in non-sports performance enhancement, suggesting that larger-scale randomized trials of similar interventions in clinical medical students may prove equally efficacious.